Medico-legal autopsy of 1355 unclaimed dead bodies brought to a tertiary care hospital in Delhi, India (2006–2012). (September 2014) - Saurav, Chopra; Aayushi, Garg; Behera, C; Karthik, Krishna; Millo, T; Gupta, SK
In India, it is estimated that about 13 million people are homeless. As these individuals have no close acquaintances, in the event of death, their bodies remain unclaimed. These unclaimed corpses pose a major challenge for the local law enforcement agencies in identification and thus become an obstacle in solving the cases of missing persons. We sought to review the autopsy characteristics and causes of death in the unclaimed/unidentified bodies autopsied at the All India Institute of Medical Sciences (AIIMS) from 2006 to 2012. Among the total of 11, 786 cases autopsied during the year 2006 to 2012, 1335 (11%) were unclaimed. Most of the cases were males (91%) with a male-to-female ratio of 9:1. Mean age of the cohort was 43 years (range, 1–85 years). Natural events were the foremost cause of death and were more commonly seen in males. While accidental, suicidal and homicidal modes were common in younger age groups; natural manner of death predominated in the elderly. Most of the cases were found dead on the roadside. This paper also compares with the previous study in the same set-up during the time period 2001 to 2005. The authors believe that knowledge about the existing healthcare facilities need to be reinforced and their utilisation promoted.